Strategi Bank Syariah Indonesia KCP Pacitan dalam Meningkatkan Minat Masyarakat Menggunakan Sistem QRIS Banking - Firly Indriani; Hanik Fitriani (Institut Agama Islam Negeri Ponorogo, 2024)
Innovation in the technology field will provide benefits, making it easier to carry out various kinds of work. The problem is the lack of public interest in using the QRIS Banking system to carry out various financial transactions. This research aims to analyze BSI KCP Pacitan's strategy in increasing public interest in using the QRIS, analyze the impact of BSI KCP Pacitan's strategy in increasing public interest in using the QRIS, and analyze the obstacles faced by BSI KCP Pacitan in marketing QRIS. This research uses a type of field research with a qualitative approach d. The research results show that the strategy carried out by Bank Syariah Indonesia KCP Pacitan in marketing QRIS Banking is to use a 4P marketing mix strategy, where QRIS is aimed at making it easier for business actors and institutions. The promotions carried out are socialization, door-to-door, brochures, and social media. The obstacle faced in marketing QRIS Banking internally is the lack of human resources to handle QRIS Banking. On the external side, namely the public's lack of understanding about QRIS, inadequate internet quota, and already having other payment applications or becoming a QRIS merchant at another bank.